Arabic Language Learning with a Communicative Approach through Massive Open Online Course Platform online.arabicgampang.id - Fitra, Muh. Naufal; Tamam, Muhammad Ibnu (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
The Massive Open Online Course (MOOC) platform is present as a new alternative to Arabic learning. MOOC is a learning platform that can be accessed openly, and is available online for anyone, anytime, and anywhere. This study aims to explore the features and uses of online.arabicgampang.id MOOC platform in Arabic language learning. The researchers used descriptive qualitative research as a research approach and observation as a data collection technique. The data that has been collected is analyzed in three stages, namely data condensation, data presentation, and depiction and conclusion drawn. Researchers found that there are various benefits in the features and use of MOOC platforms in Arabic learning, namely accessible learning, learning with a communicative approach, comprehensive evaluation, and the existence of a learning community. So, this platform offers an easy, effective, and communicative way to learn Arabic. The platform is suitable for learners of all levels, from beginner to advanced.